Analisis Pengaruh Tax Planning Terhadap Ekuitas Perusahaan - Desi Handayani (Pusat P2M Politeknik Negeri Batam, 2017)
This research aims to analyze the effect of tax planning toward equity. The data used in this research is the secondary data obtained from the financial reports of the companies listed in Indonesia Stock Exchange period 2010-2015. The sampling technique is done by using purposive sampling. From the test, it can be concluded that the percentage of corporate tax payers in Indonesia Stock Exchange which made tax planning was 53,8%. From the test result of panel data regression model coefficients with fixed effect model approach, the probability value is 0,0006 which is smaller than 0,05. This result concludes that the hypothesis is accepted, that tax planning effects significantly towards corporate equity. The R square test results show that tax planning variable can contribute in effecting the equity as much as 91,5%.